ANALISIS STRATEGI PEMASARAN PADA USAHA KECIL MENENGAH MAKANAN RINGAN (Studi kasus Dodol Mangrove di Desa Jangkang Kecamatan Bantan Kabupaten Bengkalis) - Sari, Rini Arvika (Komunitas Manajemen Kompetitif, 2020)
Marketing strategy is one way to achieve competitive advantage on an ongoing basis. Marketing strategies can be used as one of the bases for putting together company plans. for the progress and development of business in the community, it is necessary to have good planning to be used as a guideline for the segment of the community work unit in carrying out its activities, another reason for the importance of marketing strategies is the fierce competition in the community's work business in general. This research aims to: get a picture of the right marketing strategy for the products of rural communities and to find out how effective the implementation of the marketing strategy has been carried out. This research was conducted in the work unit of the Barokah community in the jangkang village. The technique of collecting data was documentation, interviews and observations. a type of descriptive study. The results of the analysis of the effectiveness of marketing strategies show an increase in total sales from year to year and serve as a reference for the effectiveness of marketing strategies in competition between work units in the community.